Stock Market Behaviour Around Buyback Announcements in India: An Empirical Justification for Preferring the Open Market Repurchase Mode - Rajagopalan, N. V. R.; Shankar, H. (Indian Journal of Finance, 2012)
In order to rationalize the capital structure, a landmark legislative adjustment was made in 1998 by making amendments in the Companies Act, 1956 for allowing buyback of shares already issued to the public. Thus, from the year 1999, the new corporate information relating to buybacks started arriving at the stock market in India. This study aims at enquiring about the reaction of the stock market to the buyback announcements for a period of 10 years from 2000-01 and 2009-10 by taking S&P CNX 500 companies in terms of returns among Open Market Repurchases (OMR) and Fixed Price Tenders (FPT). By applying standard event study procedure, the information signalling of buybacks and semi - strong efficiency test to verify the absence of abnormal returns continuously has been taken up. Having recorded a statistically significant abnormal return of 1.32% on the announcement day, and a cumulative abnormal return of 5.13% in -10 to +10 event frame, the OMRs end up with a cumulative abnormal return of 6.11% for a 61 days event window to have a strong signalling to the market. The near same abnormal return of 1.30% in FPT announcements was not statistically significant on the announcement day. The cumulative abnormal return of 2.13% in -2 to +2 frame and the negative 15.64% observed in a 61 days window evidenced a weak signalling of FPTs. In spite of having strong signalling to the market, the OMRs recorded mixed abnormal returns in a positive and negative spread around the shorter version of the event window (-10 to +10), thereby curtailing the opportunities of earning abnormal returns on a sustainable way to support the semi-strong efficiency of the market.